p63: A Master Regulator at the Crossroads Between Development, Senescence, Aging, and Cancer - Lakshana Sruthi Sadu Murari; Sam Kunkel; Anala Shetty; Addison Bents; Aayush Bhandary; Juan Carlos Rivera-Mulia (Cells)
The p63 protein is a master regulatory transcription factor that plays crucial roles in cell differentiation, adult tissue homeostasis, and chromatin remodeling, and its dysregulation is associated with genetic disorders, physiological and premature aging, and cancer. The effects of p63 are carried out by two main isoforms that regulate cell proliferation and senescence. p63 also controls the epigenome by regulating interactions with histone modulators, such as the histone acetyltransferase p300, deacetylase HDAC1/2, and DNA methyltransferases. miRNA-p63 interactions are also critical regulators in the context of cancer metastasis. This review aims to elaborate on the diverse roles of p63, focusing on disease, development, and the mechanisms controlling genome organization and function.